METHODS OF ORGANIZATION OF PROJECT ACTIVITIES IN FUTURE TEACHERS ON THE BASIS OF TUTORING SKILLS - Anvarovna Xolmatova, Ziroat (European Journal of Life Safety and Stability (2660-9630), 2021)
Currently, the Uzbek higher school, as an institution reflecting the compliance of the results and various aspects of the pedagogical activity of an educational institution with the state educational standard, the needs and expectations of society, personality, production, is looking for answers to the challenges of modern reality. It can be argued that the content of higher education is being significantly updated; it already operates within the framework of a new paradigm that works to increase student mobility, to expand their opportunities for inclusion and involvement in educational and research networks, helps to educate individual, motivated students.